Hierarchically porous carbon foams from pickering high internal phase emulsions. (May 2016) - Woodward, Robert T.; Fam, Derrick W.H.; Anthony, David B.; Hong, Jindui; McDonald, Tom O.; Petit, Camille; Shaffer, Milo S.P.; Bismarck, Alexander
Abstract: Carbon foams were produced from a macroporous poly(divinylbenzene) (poly(DVB) precursor, synthesized by polymerizing the continuous but minority phase of water-in-oil high internal phase emulsions (HIPEs) stabilized by molecular and/or particulate emulsifiers. Both permeable and non-permeable hierarchically porous carbon foams, or 'carboHIPEs', were prepared by carbonization of the resulting macroporous polymers at 800 °C. The carbon yields were as high as 26 wt.% of the original polymer. CarboHIPEs retain the pore structure of the macroporous polymer precursor, but with surface areas of up to 505 m 2 /g and excellent electrical conductivities of 81 S/m. Contrary to some previous reports, the method does not require further modification, such as sulfonation or additional crosslinking of the polyHIPE prior to carbonization, due to the inherently crosslinked structure of poly(DVB). The use of a pourable, aqueous emulsion-template enables simple moulding, minimises waste and avoids the strong acid treatments used to remove many conventional solid-templates. The retention of the macroporous structure is coupled with the introduction of micropores during carbonization, producing hierarchically porous carboHIPEs, suitable for a wide range of applications as sorbents and electrodes.